Resilience and adaptability of social workers in health care settings during COVID-19 in Australia. (21st April 2022) - Joubert, Lynette; Hampson, Ralph; Acuto, Rebecca; Powell, Lauren; Latiff, Muhammad Noor Latasa Abdul; Tran, Linh; Cumming, Sue; Dunn, Patrick; Crehan, Scott; Flewellen, Rashid; Boddenberg, Emeil; Ng, Wing Sum; et al.
ABSTRACT: In 2020 Coronavirus disease (COVID-19) was identified in Australia. During the pandemic, as essential workers, hospital-based social workers have been on the frontline. This cross-sectional study examines the resilience of social workers during the COVID-19 pandemic, how the pandemic impacted on social work and lessons learnt. Hospital social workers working in three states, namely Victoria, Queensland, and New South Wales were invited to participate in an online web-based survey, providing non-identifiable demographic details and information a) relating to their proximity to COVID-19, b) their degree of resilience (CD-RISC-2), c) professional quality of life, d) perceived social support, e) physical health, f) professional and personal growth during the pandemic, and g) impacts of COVID-19 on their practice. Basic descriptive statistics were computed for variables of interest. Within group, comparisons were made using paired t-tests or one-way ANOVAs for continuous variables as appropriate to investigate possible interstate differences. Regression analyses were conducted to determine which factors contribute to resilience. Social workers, during the pandemic, whether working under the constraints of lockdown or not, demonstrated high levels of resilience. These levels were similar across the three states, unaffected by the degree of infection in the community, indicating that as a group, social workers have high innate levels of resilience. This study provides an in-depth understanding of the impact of COVID-19 on hospital social workers, the long-term impact of the pandemic on social work practice, and potentially useful lessons learnt for the future.